(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In India, the potential for significant life insurance market expansion is in tandem with higher disposable income and a relatively young population will drive sales for both savings and protection products in the years to come. But in the recent years, despite of strong market fundamentals, private sector life insurance companies are struggling hard in maintaining a regular growth of business. Besides, the life insurance sector needs to continue on the path of innovation by designing new products suitable for the market and make use of innovative distribution channels to reach a broader range of the population. Thus it’s imperative to analyze the present marketing practices of service providers. Many a time, marketers are found to be myopic about the customers’ expectations and service quality delivered. In the light of observed facts, presented study made an attempt to identify the perception of marketers regarding level of expectation as well as perception of service quality in Indian life insurance industry by using service quality model suggested by Sureshchandar et al. (2001). The findings suggest that there exist a significant negative gap in service quality expected and perceived by the customers of life insurance services.